2021
DOI: 10.3390/mi12111320
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer-Graphene-Based Tunable Absorber in the Near-Infrared

Abstract: In this paper, a tunable absorber composed of asymmetric grating based on a graphene-dielectric-metal structure is proposed. The absorption of the absorber can be modified from 99.99% to 61.73% in the near-infrared by varying the Fermi energy of graphene, and the absorption wavelength can be tuned by varying the grating period. Furthermore, the influence of other geometrical parameters, the incident angle, and polarization are analyzed in detail by a finite-difference time-domain simulation. The graphene absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Since monolayer graphene was first mechanically exfoliated from graphite in 2004 [1], its excellent physical, chemical, and mechanical properties have attracted extensive attention [2][3][4][5][6][7]. At the same time, the graphene-like two-dimensional (2D) transition metal dichalcogenides (TMDCs) have attracted widespread attention due to their single-layer characteristics and their excellent mechanical properties similar to those of graphene [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Since monolayer graphene was first mechanically exfoliated from graphite in 2004 [1], its excellent physical, chemical, and mechanical properties have attracted extensive attention [2][3][4][5][6][7]. At the same time, the graphene-like two-dimensional (2D) transition metal dichalcogenides (TMDCs) have attracted widespread attention due to their single-layer characteristics and their excellent mechanical properties similar to those of graphene [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored the coupling of graphene to plasmonic structures, mostly in the infrared region. It has been demonstrated that graphene can be used to modulate the plasmonic response by modifying the dielectric properties. This can be achieved by both electrical gating and chemical doping. When the graphene layer overlaps with the electric field hot spot, it can have remarkable effects on the modulation of the plasmonic spectra, even in the visible wavelength range. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…However, it is not typically utilized as a laser absorber. Given graphene's zero-band-gap structure, where the conduction band and valence band intersect, and the presence of a large number of conjugate systems (consisting of numerous benzene ring structures) in the graphene molecular structure, graphene can exhibit remarkably broad spectral absorption bands [17,18]. Graphene demonstrates pronounced nonlinear and strong light absorption when subjected to intense illumination [19].…”
Section: Introductionmentioning
confidence: 99%